1997
DOI: 10.1038/sj.jhh.1000392
|View full text |Cite
|
Sign up to set email alerts
|

A dose-response trial of nebivolol in essential hypertension

Abstract: A double-blind placebo-controlled dose-response trial clear inferiority of efficacy in black patients. A single of nebivolol, a cardioselective beta-blocking drug which daily dose of 5 mg was appropriate, with no evident also induces endothelium-dependent dilatation via nitric advantage at 10 mg. The drug was well tolerated, even oxide, has been performed. Nebivolol reduced blood at 10 mg daily. BP control was achieved largely in the pressure (BP) in a dose dependent way, and was shown absence of typical side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 3 publications
2
23
0
2
Order By: Relevance
“…6,14,15 Nebivolol also provided significant dose-dependent BP reductions in clinical trials in hypertensive patients and was safe and well tolerated. 6,14,[16][17][18][19] The objective of this study was to assess the BPlowering efficacy and safety of once-daily nebivolol added to ongoing antihypertensive therapy in patients with uncontrolled stage I-II hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…6,14,15 Nebivolol also provided significant dose-dependent BP reductions in clinical trials in hypertensive patients and was safe and well tolerated. 6,14,[16][17][18][19] The objective of this study was to assess the BPlowering efficacy and safety of once-daily nebivolol added to ongoing antihypertensive therapy in patients with uncontrolled stage I-II hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…It acts partly through the l-arginine/nitric oxide pathway, has vasodilating effects, and iod, the increase in fatigue was found to be more prominent with atenolol than with nebivolol or plaimproves large arterial compliance. [1][2][3][4][5][6][7][8][9][10]12 Nebivolol has been shown to enhance left ventricular function cebo (Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…A previous dosewith vasodilating properties and a prolonged action; response trial of nebivolol had shown that 5 mg it acts in part via the l-arginine/nitric oxide pathonce daily in hypertensive patients controlled blood way. At similar anti-hypertensive doses, nebivolol pressure (BP) over 24 h; no additional effect was has been found to exert less beta-1 blockade than do seen with 10 mg. 10 Likewise, atenolol 50 mg once standard beta-blockers, as judged by the extent of daily had earlier been found to be as effective as reduction of exercise-induced tachycardia. [1][2][3][4][5][6][7][8][9] This 100 mg. 11 Thus the doses of active drugs used were paper reports a double-blind randomised trial of nebivolol 5 mg and atenolol 50 mg.…”
Section: Introductionmentioning
confidence: 99%
“…A large observational study of nebivolol monotherapy in patients with hypertension (N = 6376) found that the rate of response in patients older than 65 years and older than 75 years (92.9% in both) was similar to that in patients younger than 65 years (92.8%) [53]. In addition, a large, randomized, placebo-controlled, dose-ranging study (N = 509) found that nebivolol had similar efficacy in hypertensive black patients as in white patients, with average BP reductions at trough of -9.7/8.5 mm Hg and -9.0/9.4 mm Hg, respectively [54].…”
Section: Blood Pressure Reductionmentioning
confidence: 74%